Household survey on agency and governance in Maharashtra, India - Justino, Patricia (UK Data Service, 2014)
This is a socio-economic household survey dataset which was collected in urban centres in the state of Maharashtra, India. The dataset covers information about social capital and cooperation, household assets, the household’s experience of urban riots and various other shocks, perceptions of safety, coping strategies, and specific demographic information for each household member. The main purpose of this study is to fill this theoretical, empirical and policy gap by analysing how the relationship between populations living in contexts of violence and armed non-state actors controlling or contesting those areas results in forms of local governance and order, and how these in turn affect the access to and effectiveness of livelihoods adopted by individuals and communities in contexts of violence. The study is based on comparative qualitative and quantitative empirical work in Colombia, India, Lebanon, Niger and South Africa.